\((19 \sqrt{h} +{4\sqrt{2h}})(19\sqrt{h} - 4\sqrt{2h)}\)

and explain the multiplication process

Guest Sep 27, 2017

#1**0 **

simplify | (19 sqrt(h) + 4 sqrt(2 h)) (19 sqrt(h) - 4 sqrt(2 h))

361h - 76sqrt(2)h + 76sqrt(2)h - 32h

361h - 32h

**329h**

Guest Sep 27, 2017

#2**+1 **

Note that (a + b)(a - b) = a^{2} - b^{2}

So... \(({\color{violet}\,19\sqrt{h}} + {\color{blue}4\sqrt{2h}})({\color{violet}\,19\sqrt{h}} - {\color{blue}4\sqrt{2h}})\,=\,({\color{violet}\,19\sqrt{h}})^2-( {\color{blue}4\sqrt{2h}})^2\)

\((\,19\sqrt{h})^2-( 4\sqrt{2h})^2 \\~\\ =\,19*19*\sqrt{h}*\sqrt{h}-4*4*\sqrt{2h}*\sqrt{2h} \\~\\ =\,361h-16*2h \\~\\ =\,361h-32h \\~\\ =\,329h\)

.hectictar Sep 27, 2017